ЛИЧНОСТНЫЕ ОСОБЕННОСТИ РАЗЛИЧНЫХ ТИПОВ ПРОЯВЛЕНИЯ ЖЕРТВЕННОСТИ - Анастасия КОВРОВА; Людмила АНЦИБОР (Moldova State University, 2020)
В статье описаны результаты практического исследования личностных особенностей различных типов проявления жертвенности. В рамках исследования были определены специфичные для каждого типа наборы особенностей. Предполагается, что подобная дифференциация в перспективе делает возможным более точное конструирование психокоррекционных интервенций.   THE PERSONAL FEATURES OF DIFFERENT TYPES OF VICTIM MANIFESTATION The article describes the results of the practical study of the personal particularities of the different types of victim manifestation. Within the study, sets of particularities specific to each type were identified. It is assumed that such a differentiation in perspective makes possible the more precise construction of psychocorrectional interventions.